Modificação de meios filtrantes com nanomateriais para controle de bioaerossóis - Remiro, Paula de Freitas Rosa (2018)
People are increasingly wasting their time in indoors environments, in these locations there is a risk of contagion from diseases transmitted by the airways, due to low rates of air exchange. Thus, the number of causative agents of various diseases airborne spreads more rapidly, increasing cases of respiratory problems. Therefore, controlling the microorganisms present in indoor environments has become extremely necessary. An alternative is to develop filters for air conditioners, laminar flow hoods, and clean room exhausts that have antimicrobial properties. There are numerous materials that have an action against fungi and bacteria, among them silver and titanium dioxide. By combining these two materials a composite can be formed which is expected to have a synergistic effect. Thus, this thesis had as main objective the development of modified filter media with those nanomaterials that present antimicrobial capacity. After the modification of the filters, adhesion strength analyzes and peel velocity calculations between the nanomaterials and the fibers were done in order to ensure that they are not released into the environment. The results showed that the inhibition in the real environment was 55.6 ± 9.52, 72.2 ± 4.81 and 81.1 ± 1.92%, adhesion forces 3.44, 14.32 and 12, 24 nN and the average velocities required to release the nanomaterials of 125.2, 46.8 and 35.7 m / s for the silver, titanium dioxide and Ag/TiO2 nanoparticles respectively. These data suggest a considerable decrease in the number of microorganisms when using filters modified with these nanomaterials and have shown that the particles are removed at different speeds. However, with the results obtained it was not possible to point to a filter that satisfies all the evaluated parameters. The Ag/TiO2 modified filter showed greater inhibition capacity of the microorganisms, however, this material can be removed at lower speeds when compared to the other materials. The silver filter has the lowest inhibition rates, but high velocities are required to remove the particles adhered to it. Thus, the most appropriate filter is one that satisfies the operating conditions of the equipment on which it will be used.